PERAN SUMBER DAYA MANUSIA DALAM KELOMPOK TANI TANAMAN HIAS GAPOKTAN TOGA KELURAHAN MAHAKERET BARAT - Fransisco Pitar; Charles R. Ngangi; Jenny Baroleh (COCOS, 2015)
ABSTRACTPitar Francisco. Role of Human Resource Farmers Group Gapoktan Toga Ornamental Plants in Sub Mahakeret West (under the guidance of Charles R. Ngangi as Chairman, Jenny Baroleh as Members).In the role of human resources in agricultural development itself get special attention to the holding of a wide range of specialized training on HR itself and run seminars that discuss HR agriculture. Areas where regional autonomy as the executor of agricultural development requires the number of agricultural institutions and adequate human resources. So far, the facts show less agricultural development a priority of development in the area, but now the role of HR agriculture began note if this continued and sustained it meets the needs of human resources capable of existing needs.These results indicate that the role of human resources in the toga gapoktan more active role than in the less active that 16 people were declared inactive by the number of above-average score of more than 10 and less active as many as four people with a total score of below average -rata less than 10, while the inactive otherwise no. From the results of this study revealed that the assessment of the role of Human Resources (HR) in the group of ornamental (Gapoktan Toga) in the Village of West Mahakeret expressed an active role in carrying out their respective roles.